A methodological approach to assess the territorial vulnerability in terms of people and road characteristics. Issue 2 (3rd April 2022) - Maletta, Roberta; Mendicino, Giuseppe
ABSTRACT: The objective of this paper is to develop an assessment model for territorial vulnerability by measuring the spatial heterogeneity of proper indicators that amplify the natural and manmade hazards. The proposed study was carried out through an evaluation of the following components: people characteristics, emergency plan elements, operational structures of civil protection, and road infrastructure. A methodological approach was implemented to analyse the inhabitants, workers and other users' vulnerabilities, combining these with road network vulnerability. The application of a GIS-based model was used to capture, analyse, and manage the spatial data recorded on different scales and to visualise vulnerability results. A case study was proposed regarding a municipal area in Southern Italy that is frequently affected by floods and landslides which cause damage to the road network, limiting access to structures and resources. Results show how strategies and responses to emergency management will be different in each community and need to be reviewed as part of regular planning and prevention activities. The proposed study aims to create a tool that can be adjusted to user-specific needs to support decision-making, to reduce risk, and for disaster management at the local levels.